2018
DOI: 10.1111/1467-9566.12749
|View full text |Cite
|
Sign up to set email alerts
|

The categorisation of resistance: interpreting failure to follow a proposed line of action in the diagnosis of autism amongst young adults

Abstract: Many characteristics typical of autism, a neurodevelopmental condition characterised by socio-communicative impairments, are most evident during social interaction. Accordingly, procedures such as the Autism Diagnosis Observation Schedule (ADOS) are interactive and intended to elicit interactional impairments: a diagnosis of autism is given if interactional difficulties are attributed as a persistent quality of the individual undergoing diagnosis. This task is difficult, first, because behaviours can be interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…We have found, in line with these researchers, that clinicians foreground discussion of behaviours that are ‘story‐worthy’ and these include both their own observations as well as harnessing informant testimony that contribute to the diagnostic account. We also found, in line with Hollin and Pilnick's () study, that, in the process of retelling the behavioural story, clinicians interpret that behaviour in the light of autistic behaviours.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We have found, in line with these researchers, that clinicians foreground discussion of behaviours that are ‘story‐worthy’ and these include both their own observations as well as harnessing informant testimony that contribute to the diagnostic account. We also found, in line with Hollin and Pilnick's () study, that, in the process of retelling the behavioural story, clinicians interpret that behaviour in the light of autistic behaviours.…”
Section: Discussionsupporting
confidence: 89%
“…However, a UK study by Hollin and Pilnick () found that the diagnostic decision can shift depending on how similar types of behaviour are interpreted. In ADOS assessment sessions, facilitated by ADOS‐trained researchers, they demonstrate how judgments are made about which kinds of behaviour are consequential for diagnosis.…”
Section: Talk Between Healthcare Practitioners About Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Fombonne ) – it would invariably involve the workings of the clinic, making relevant a social‐interactional explication of its organisation, such as we have provided here and in related studies (Maynard and Turowetz , forthcoming, Turowetz and Maynard , cf. also Hollin and Pilnick's () study of clinical testing and interpretation using the ADOS).…”
Section: Discussionmentioning
confidence: 97%
“…For example, the Autism Diagnosis Observation Schedule (ADOS; Lord et al 1989, 2000) is often described as the “gold standard” diagnostic instrument within both clinical and research settings (Fombonne 2009, 592; Norbury and Sparks 2013, 7) and would be an obvious tool to gather the behavioral data required to interpret genomic analyses. An ADOS session takes around forty minutes to complete and requires two highly trained observers who attend and rewatch and discuss diagnostic sessions (Hollin and Pilnick 2018). Such a process is simply too time- and resource-intensive for many of the studies imagined within genomics, which require huge sample sizes.…”
Section: Endophenotypes and The Need For Novel Diagnosticsmentioning
confidence: 99%